PENENTUAN HASIL EVALUASI PEMILIHAN SPESIES POHON DALAM PENGENDALIAN POLUSI UDARA PABRIK SEMEN BERDASARKAN KARAKTERISTIK MORFOLOGI - Azzahro, Fiona (Journal of Research and Technology, 2019)
The rapid development of the country in Indonesia, especially in the fields of industry and technology, is inseparable from the problem of air pollution, especially in the environment, namely pollutant gas and dust. Air pollution needs to be environmentally friendly by increasing the amount of vegetation or reforestation by planting tree species that have the ability to grow and absorb pollutant gases and absorb dust particles in polluted environmental conditions. The study uses descriptive analysis by assessing tree elements macroscopically to select the appropriate tree species and can be recommended as an absorber of gas pollutants and dust absorbers based on tree suitability scoring. The results showed that of 7 (seven) dominant tree species identified, there were 3 (three) dominant tree species that were very suitable, 3 (three) dominant tree species were suitable, and only 1 (one) dominant tree species were not suitable for air pollutant gas. Whereas the evaluation of the function of dust particle absorption shows that all dominant tree species studied have the appropriate criteria in absorbing dust with the acquisition of 65% -75% evaluation value.